Digital Teaching Materials for Explanatory Texts to Strengthen Critical Thinking for High School Students - Purwaningsih, Tri Wahyuni; Rozak, Abdul; Wiradinata, Rochanda (PT Inovasi Pratama Internasional, 2024)
This research aims to develop digital teaching materials for explanatory texts to strengthen high school students' critical thinking. Formulation of the problem of this research (1) How do digital explanatory text teaching materials strengthen critical thinking? (2) What are the results of implementing digital explanatory text teaching materials to strengthen critical thinking? This research uses research and development methods with the ADDIE model. The steps in this research consist of needs analysis, designing digital teaching materials, developing digital teaching materials, implementing digital teaching material products, and evaluating digital teaching material products. The method for collecting data in this research is by collecting data from the results of expert validation questionnaires and student assessment questionnaires. The data obtained was analyzed descriptively using a Likert scale. The results of the design of digital teaching materials for explanatory texts to strengthen high school students' critical thinking consist of cover, material, post-material, Canva video, and accompanied by musical instruments that can be accessed using a computer or smartphone. The results of product assessments by validity experts (materials, media and teachers) as well as the results of student questionnaires regarding digital teaching material products with explanatory texts are stated in the